CONSERVATIVE MANAGEMENT PELVIC FRACTURE URETHRAL INJURY (PFUI) IN A GIRL: A CASE REPORT - Sulistyanti, Rachma Fitri; Satyagraha, Paksi; Nurhadi, Pradana; Daryanto, Besut (Indonesian Journal of Urology, 2023)
ABSTRACT Objective: This case report aims to describe a different approach of PFUI by conservative management that resulted in good outcome. Case(s) Presentation: A 7-year-old girl patient was brought to the emergency department after falling from public transportation diagnosed with suspicious urethral rupture, perineal rupture grade III, vertical-shear type pelvic-ring injury, laceration wound on the right lower leg, abrasion on the medial side left lower leg and urinary retention. The patient underwent percutaneous cystostomy, pelvic bandage, a perineal debridement and repair, a cystography, percutaneous vesicolithotripsy, cystostomy and synechiae incision. One year after the first admission it was planned for urethroplasty due to completely obliterated from antegrade and retrograde panendoscopy. Discussion: 8 months later urethroplasty was aborted because of an open bladder neck, a fistula at the anterior connected to the distal of the bladder neck with size of 3 mm. The patient was performed a silicon cystostomy catheter insertion for 6 weeks. At the time of evaluation, the fistula was closed, it was proven by Qmax uroflowmetry was 18ml/s with average flow: 9.8 ml/s, voiding volume: 90ml, flow time: 9s, voiding time: 9s, hesistance:1.5, and PVR:5.35 cc. Conclusion: In this case, it showed that conservative management could improve PFUI with satisfactory result, proved by good result of uroflowmetry. However, periodic evaluations must be carried out to follow the progress of the disease and the possibility of future complications including sexual function. Keywords: PFUI, girl, urethral rupture